Meta‐analysis of the demographic and prognostic significance of gastrointestinal symptoms in COVID‐19 patients. Issue 10 (29th August 2022) - Zaman, Shafquat; Hajibandeh, Shahin; Hajibandeh, Shahab; Mohamedahmed, Ali Yasen Y; El‐Asrag, Mohammed E; Quraishi, Nabil; Iqbal, Tariq H; Beggs, Andrew D
Abstract: Background and Aim: To evaluate the demographic and prognostic significance of gastrointestinal (GI) symptoms in patients with coronavirus disease 2019 (COVID‐19). Methods: A systematic search of electronic information sources was conducted. Combined overall effect sizes were calculated using random‐effects models for baseline demographic factors and outcomes including mortality, intensive care unit (ICU) admission, and length of hospital stay. Results: Twenty‐four comparative observational studies reporting a total of 51 522 COVID‐19 patients with ( n  = 6544) or without ( n  = 44 978) GI symptoms were identified. The patients with GI symptoms were of comparable age (mean difference [MD]: 0.25, 95% confidence interval [CI] −2.42 to 2.92, P  = 0.86), rate of pre‐existing hypertension (odds ratio [OR]: 1.11, 95% CI 0.86–1.42, P  = 0.42), diabetes mellitus (OR: 1.14, 95% CI 0.91–1.44, P  = 0.26), and coronary artery disease (OR: 1.00, 95% CI 0.86–1.16, P  = 0.98) compared with those without GI symptoms. However, there were significantly more male patients in the GI symptoms group (OR: 0.85, 95% CI 0.75–0.95, P  = 0.005). The presence of GI symptoms was associated with similar risk of mortality (OR: 0.73; 95% CI 0.47–1.13, P  = 0.16), ICU admission (OR: 1.15; 95% CI 0.67–1.96, P  = 0.62), and length of hospital stay (MD: 0.43; 95% CI −0.73 to 1.60, P  = 0.47) when compared with their absence. Conclusion: Meta‐analysis of the best possible available evidence demonstrated that GI symptoms in COVID‐19 patients do not seem to affect patients with any specific demographic patterns and may not have any important prognostic significance. Although no randomized studies can be conducted on this topic, future high‐quality studies can provide stronger evidence to further understand the impact of GI symptoms on outcomes of COVID‐19 patients. Abstract : Meta‐analysis of the best possible available evidence demonstrated that gastrointestinal symptoms in COVID‐19 patients do not seem to affect patients with any specific demographic patterns and may not have any important prognostic significance.